PSYCHOSPIRITUAL FOUNDATIONS OF ECONOMIC TRANSFORMATION : (A Case Study of Al-Kayyis Islamic Boarding School in Lebak, Banten) - Rudin, Syah; Zakiah Mohamad Ashari; Roni Susanto; Rofiq Husnul Maafi (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This study examines the role of psychospiritual foundations in the economic transformation of the laying-hen business unit at Pondok Pesantren Al-Kayyis, Sajira, Lebak, Banten, as a representation of the integration between spirituality and economic rationality in pesantren-based empowerment. Prior to participating in the business incubation program, the enterprise faced structural and technical constraints such as limited capital, high feed prices, dependence on factory products, simple facilities, and a small production scale. Through the incubation program, Al-Kayyis successfully doubled its production capacity, developed locally sourced alternative feed (a mixture of rice bran, moringa leaves, petai cina, and itigovera), diversified its market toward local communities and students’ guardians, and implemented a sharia-based profit-sharing system that strengthened transparency and justice. Ecological innovation—such as using geese as natural guardians—reflected the synergy between simple technology and local wisdom. Using a qualitative descriptive approach with a single-case study design, data were collected through in-depth interviews, participatory observation, and field documentation. The findings reveal that the success of the economic transformation was driven not only by managerial and technical improvements but also by psychospiritual strength that infused every economic activity. The values of dzikr, patience, reliance on God (tawakal), gratitude, and ihsan functioned as psychological capital, nurturing work ethics, resilience, and spiritual awareness among students. The integration of spirituality, ethical production, and local innovation created a model of Sufistic economy—an economic system grounded in tasawuf that harmonizes productivity, sustainability, and blessing. The study contributes to the development of living Sufism and Islamic psychology by positioning spirituality as an alternative rationality in economic decision-making and a transformative source for pesantren-based economic empowerment.